NON-TRANSECTING ANASTOMOTIC BULBAR URETHROPLASTY FOR URETHRAL STRICTURE DISEASE-EXPERIENCE FROM A HIGH-VOLUME SPECIALIST CENTRE - Memon, Imran; Soomro, Kashifuddin Qayoom; Rajpar, Zakir Hussain; Abdullah, Aziz (Journal of Ayub Medical College Abbottabad, 2020)
Background: Urethral stricture disease has significant economic impact throughout world. The bulbar urethra is the commonest site for urethral strictures (Approx 50%) followed by penile urethra in most of the published literature.In developing countries trauma (road traffic accident and iatrogenic) is the leading cause of urethral stricture disease.Younger patients have usually idiopathic type as compare to old age group, which present more frequently with iatrogenic and trauma related urethral strictures. Methods: This Qausi Experimental study was conducted from May2012-June2016 of duration at Liaquat National Hospital Karachi. All the patients diagnosed with short urethral strictures related to bulbar urethra were included in this study. All the patients underwent non transecting bulbar urethroplasty. All patients were assessed preoperatively, peri-operatively and postoperatively and on follow-up visits as; on 2nd, 8th and 24th week. All the data regarding outcome was recorded on the Performa and analyzed on SPSS V20. Results: Total of 179patients were included, mean age was 38±SD15.3years (range 20-65years). Anatomically bulbar urethra was affected in 52% of the cases followed by bulbopenile, bulbomembranous region. Etiologically idiopathic type was found in 40% cases, while trauma 21%, iatrogenic injury 26% and UTI 13% were also reasons. Stricture length was mean1.1±SD 1.4 cm (range 0.5-2.5cm). Preoperative Uroflowmetry revealed mean Qmax of 10.5±SD 5.3 ml/sec. Mean operative time was 35±SD 4.6 minutes, 7 patients had conversion to other procedures (3.91%), Postoperative complications were minimal. Mean follow up was 12±SD 21 months (range 6 months to 3 years). On initial follow up at 8th week and 24th week, Qmax was significantly improved. Only 3 patients required DVIU after the 24th week. Initial success rate after 24th week was 98.3% and eventually 100% at the long-term follow-up. Conclusion: non-transecting anastomotic bulbar urethroplasty (NTABU) is a new standard of care for the short bulbar urethral stricture up to 2.5cm. Idiopathic aetiology, iatrogenic and posttraumatic urethral strictures in selective patients can safely be operated with this technique. Keyword: Non-transecting; bulbar Urethroplasty; Urethral strictures